ESMO expert consensus statements on the management of EGFR mutant non-small-cell lung cancer - Passaro, A; Leighl, N; Blackhall, F; Popat, S; Kerr, K; Ahn, M J; Arcila, M E; Arrieta, O; Planchard, D; de Marinis, F; Dingemans, A M; Dziadziuszko, R; et al. (Annals of oncology, 2022)
The European Society for Medical Oncology (ESMO) held a virtual consensus-building process on epidermal growth factor receptor (EGFR)-mutant non-small-cell lung cancer in 2021. The consensus included a multidisciplinary panel of 34 leading experts in the management of lung cancer. The aim of the consensus was to develop recommendations on topics that are not covered in detail in the current ESMO Clinical Practice Guideline and where the available evidence is either limited or conflicting. The main topics identified for discussion were: (i) tissue and biomarkers analyses; (ii) early and locally advanced disease; (iii) metastatic disease and (iv) clinical trial design, patient's perspective and miscellaneous. The expert panel was divided into four working groups to address questions relating to one of the four topics outlined above. Relevant scientific literature was reviewed in advance. Recommendations were developed by the working groups and then presented to the entire panel for further discussion and amendment before voting. This manuscript presents the recommendations developed, including findings from the expert panel discussions, consensus recommendations and a summary of evidence supporting each recommendation.